Japan Administered Account for Selected IMF Activities (JSA) : Annual Report for Fiscal Year 2009. (International Monetary Fund, 2009)
This paper provides a brief description of the IMF and its activities, focusing in particular on its technical assistance (TA) activities. The report then describes in greater detail the Japan Administered Account for Selected Fund Activities (JSA)-including its scope and objectives, the size and uses of the TA contribution, and assessments of its TA activities and scholarship programs-with a focus on fiscal year (FY) 2009. Japan has provided grant contributions to support IMF technical assistance to member countries since 1990. In 1997, the scope of the administered account was widened to allow for financing other IMF activities in Asia and the Pacific, carried out through the IMF Regional Office for Asia and the Pacific in Tokyo. Regular consultations are held between the IMF and the Japanese authorities; the most recent formal meeting took place in April 2009. The use of JSA resources is flexible. JSA funds can be used to cover the cost of short- and long-term TA experts and other costs associated with conducting seminars and workshops, such as room rental fees.